Penyeberang Sempadan - Anwar Ridhwan (Utusan Publications & Distributors, 2012)
The story is focused on magical narrative about a protagonist who claims to be a "defender and fighter" of the homeland, a crosser of geographical and ideological borders who finally arrives back at the origin of truth